Enhanced mechanical properties of SiC/Al composites at cryogenic temperatures. Issue 3 (15th February 2019) - Liu, Qiuyuan; Wang, Feng; Wu, Weiwei; An, Di; He, Zhiyong; Xue, Yanpeng; Zhang, Qifu; Xie, Zhipeng
Abstract: In this study, silicon carbide particulates reinforced Al matrix (SiC/Al) composites was prepared by the pressureless infiltration technique. The phase transformation and mechanical properties of SiC/Al compositess were observed at different cryogenic temperatures. With the temperature decreasing, the phase composition retained the same and no new diffraction peaks were detected. The mechanical properties of the samples were improved at cryogenic temperatures. Upon decreasing the temperature from 293 K to 77 K, the flexural strength increased from 289.08 ± 21.58 MPa to 353.46 ± 18.75 MPa, and fracture toughness went up from 7.52 ± 0.72 MPa m 1/2 to 9.26 ± 0.53 MPa m 1/2, respectively. The enhancement of mechanical properties was due to the elastic modulus increasing. Possessing the excellent mechanical properties at cryogenic temperatures, SiC/Al composites could have potential applications in cryogenic environment.